Hybrid simulation of a multi‐span RC viaduct with plain bars and sliding bearings. (6th April 2015) - Abbiati, Giuseppe; Bursi, Oreste S.; Caperan, Philippe; Di Sarno, Luigi; Molina, Francisco Javier; Paolacci, Fabrizio; Pegon, Pierre
Summary This paper deals with the seismic response assessment of an old reinforced concrete viaduct and the effectiveness of friction‐based retrofitting systems. Emphasis was laid on an old bridge, not properly designed to resist seismic action, consisting of 12 portal piers that support a 13‐span bay deck for each independent roadway. On the basis of an OpenSEES finite element frame pier model, calibrated in a previous experimental campaign with cyclic displacement on three 1:4 scale frame piers, a more complex experimental activity using hybrid simulation has been devised. The aim of the simulation was twofold: (i) to increase knowledge of non‐linear behavior of reinforced concrete frame piers with plain steel rebars and detailing dating from the late 1950s; and (ii) to study the effectiveness of sliding bearings for seismic response mitigation. Hence, to explore the performance of the as built bridge layout and also of the viaduct retrofitted with friction‐based devices, at both serviceability and ultimate limit state conditions, hybrid simulation tests were carried out. In particular, two frame piers were experimentally controlled with eight‐actuator channels in the as built case while two frame piers and eight sliding bearings were controlled with 18‐actuator channels in the isolated case. The remaining frame piers were part of numerical substructures and were updated offline to accurately track damage evolution. Copyright © 2015 John Wiley & Sons, Ltd.